Efektivitas Model Project Based Learning Berbantuan Canva Terhadap Kemampuan Komunikasi Matematis Siswa - Sudianto, Sudianto; Yaqin, Silpi Syamrotul (Didactical Mathematics, 2024)
Mathematical communication skills are essential for students in learning mathematics. However, field observations indicate that students' mathematical communication skills are still relatively low. This study aims to evaluate the effectiveness of the Canva-assisted project-based learning model on students' mathematical communication skills. The research employed a quasi-experimental method with a nonequivalent control group design. The population consisted of 8th-grade students at SMP IT At-Tadzkir during the 2023/2024 academic year, using simple random sampling as the sampling technique. The selected sample included Class VIII C as the experimental group and Class VIII E as the control group, with each class comprising 27 students. The findings of this study reveal that the experimental group achieved both individual and classical learning mastery. Furthermore, a significant difference was observed in the average mathematical communication skills between the experimental and control groups. Additionally, there was a notable difference in the improvement of mathematical communication skills between students who were taught using the Canva-assisted project-based learning model and those who were taught using conventional methods. Therefore, the project-based learning model is effective in enhancing students' mathematical communication skills.